More baking problems solved - Cauvain, Stanley P. (CRC Press ; Woodhead Pub., 2009)
Annotation When things go wrong in the bakery, the pressures of production do not allow time for research into the solution. Solving these baking problems has always been the province of 'experts'. However, with a methodical approach, keen observation and a suitable reference book then the answers to many baking problems are more easily identified. The companion volume to the popular Baking problems solved, More baking problems solved contains an updated guide to problem solving and the answers to further frequently asked questions Once again arranged in a practical question-and-answer format, it will enable busy bakery professionals to understand causes of their problems and implement solutions. Written by two leading experts and based on a wealth of practical experience, More baking problems solved will be invaluable to all bakery professionals, bakery students, food technologists and product developers.
Keywords: Baking.; elektronické knihy; electronic books